Management of Pathologic Fractures Around the Hip: Part 2–Acetabulum - Auran, Richard L.; Duran, Michael D.; de Comas, Amalia M.; Jacofsky, David J. (The Journal of Hip Surgery, 2019)
Metastatic disease to the periacetabular region of the pelvis is a complex and challenging problem to treat. Similar to the proximal femur, this area of the skeleton has a high proportion of involvement when primary tumors metastasize to bone. Surgical intervention to treat this patient population is significantly more difficult than treating lesions of the proximal femur. There tends to be higher rates of intraoperative blood loss and postoperative complications, as well as poorer prognoses. It is important for the operating surgeon to evaluate the patient's medical status using a multidisciplinary approach and fully understand their prognosis before planning and performing surgical intervention. Given the complex nature of these surgeries, they are best performed by orthopaedic oncologists or experienced revision arthroplasty specialists. The clinical evaluation, workup, and perioperative adjuncts to treatment for periacetabular metastatic disease are similar to those for disease of the proximal femur as discussed in part 1 of this article series. This review focuses on aspects specific to acetabular disease and surgical intervention in these patients.
Keywords: pathologic; metastases; fracture; acetabulum; hip